Psychoneurobic programming for sustainability of mental health during lockdown - Kumar, Rajeev; Raj, Pranati; Tiwari, Chandrasekhar (Medico Research Chronicles, 2020)
Novel Coronavirus Disease (COVID-19) is an infectious disease caused by the most recently discovered coronavirus. This new virus and disease were unknown before the outbreak began in Wuhan, China in December 2019. On 11th March 2020, WHO declared the COVID-19 outbreak as a pandemic and reiterated the call for countries to take immediate actions and scale up the response to treat, detect and reduce transmission to save people’s lives. The COVID-19 global crisis has given rise to the new normal way of surviving, both personally and professionally. With individuals restricted within the four walls of their homes, mental health has taken a severe hit. Sixty-one percent of Indians are experiencing mental health-related issues because of the uncertainty and looming financial crisis during the lockdown as per the survey conducted by The Mavericks India. Women are struggling more than men as their workload has increased significantly with them carrying multiple responsibilities without any assistance from domestic helpers.It is crucial for the wellbeing of the people to lower down the effect of mental stresses to heal Psychosomatic diseases like mood, anxiety disorders, loss of memory, diabetes, obesity, hypertension, cardiovascular disease, thyroid, chronic back pain, arthritis, migraine, respiratory disorder, hepatitis, sleep disorders, kidney problems, allergies, muscular atrophy, etc. are more prevalent and the incidence of schizophrenia has increased. In the present study, it will be shown the effectiveness of Psycho Neurobics, innovative techniques designed by my Guru, and guide Dr. Chandrashekhar Tiwari, founder president of SIGFA Institute of Research and Development, Faridabad, Haryana, India, on psychosomatic disorders arising due to lockdown. The results will be statistically analyzed and the probability for complete healing will be discussed.